2021
DOI: 10.33902/jpr.2021269677
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high-stakes testing on the teaching and learning processes of mathematics

Abstract: The impacts of high-stakes testing administered within the framework of accountability policies concern all the stakeholders in the field of education, particularly the policymakers. As such, in the present study, which is specific to the mathematics course, the aim was to examine the impacts of high-stakes testing on teaching and learning processes, measurement and evaluation, communication, and motivation based on teacher perceptions. The study employed one of the qualitative research designs, namely phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…As noted, we find few such studies in the greater Cape Town low socioeconomic areas (Julie et al, 2019a). By analysing such conversational exchanges, the UMEs are likely to identify curricular details that signal to teachers what to teach, how to assess and what will be examined (Göloglu & Kaplan Keles, 2021;Jonsson & Leden, 2019). Such details provide another way of discovering how teachers converse about the intended, implemented, interpreted and examined curricula (Julie, 2013).…”
Section: Rationale For the Studymentioning
confidence: 99%
“…As noted, we find few such studies in the greater Cape Town low socioeconomic areas (Julie et al, 2019a). By analysing such conversational exchanges, the UMEs are likely to identify curricular details that signal to teachers what to teach, how to assess and what will be examined (Göloglu & Kaplan Keles, 2021;Jonsson & Leden, 2019). Such details provide another way of discovering how teachers converse about the intended, implemented, interpreted and examined curricula (Julie, 2013).…”
Section: Rationale For the Studymentioning
confidence: 99%
“…Also, Stilhan et al revealed that administrators focused on strategies to increase test scores rather than learning outcomes, which negatively affected learners [7]. Demir & Kele focused on assessing the impact of the market high-stakes testing on the teaching and learning process of mathematics [2]. They used a sample size of 13 middle school mathematics teachers.…”
Section: Forms Of Standardized Testing In Higher Educationmentioning
confidence: 99%
“…Moreover, if these test results are used to make important decisions about students, teachers, administrators and schools, they are considered high-stakes examinations. 4 According to Johnson et al , a test or test programme is high-stakes if its results determine a student’s failure or success in entering a higher grade, enabling or preventing a graduate student from attending higher educational school, and fund management. 8 Therefore, the concept of ‘high-stakes examinations’ refers to tests that are administered nationwide and worldwide in a standardised way.…”
Section: Terminologymentioning
confidence: 99%
“…Their assessment and accountability policies impact many people and institutions, such as universities, embassies, students, educators, politicians and educational stakeholders. Moreover, if these test results are used to make important decisions about students, teachers, administrators and schools, they are considered high-stakes examinations 4. According to Johnson et al , a test or test programme is high-stakes if its results determine a student’s failure or success in entering a higher grade, enabling or preventing a graduate student from attending higher educational school, and fund management 8.…”
Section: Terminologymentioning
confidence: 99%
See 1 more Smart Citation